Progressive Development of Women’s Human Rights in International Human Right Law and within United Nations System - Shazia Qureshi (Journal of Political Studies, 2012)
This article begins by briefly tracing the trajectory of women’s human rights discourse starting from the post United Nations period to the present day, within the framework of International law institutions (Kelly, 2005, December: 475; Rampton, 2008 ). It will get insight into the process of reorientation of human rights law through the development of key International instruments that have caused to materialise the concept of women’s human rights. The strengths and weaknesses of the Convention on the Elimination of All Forms of Discrimination against Women will particularly be highlighted by comparing the Treaty with some of the mainstream human rights instruments. The article will focus on the recent increase in the efforts for gender mainstreaming in the various United Nations’ bodies. Finally it will argue that in order for any real progress to be made in terms of eradicating the systemic barriers to gender justice and to eliminate the constructive denial of women’s rights, the human rights regime must reconfigure its approaches in addressing the needs of women globally.